Donation Florence & Daniel Guerlain : Musée National d'art moderne - Cci - Centre Pompidou, Paris. - Persman, Joanna; Nordal, Bera (Skärhamn : Nordiska akvarellmuseet, 2015)
Banerjee, Rina ; Bauer, Marc ; von Brandenburg, Ulla ; Bächli, Silvia ; Dietman, Erik ; Dion, Mark ; Dumas, Marlene ; Dzama, Marcel ; Gastaldon, Vidya ; Yong Ping, Huang ; et al.
Nordiska akvarellmuseet, Skärhamn, 20.9.2015 - 28.2.2016
boek